Is It a Professional Career or Job? Using Sketch Engine to Investigate Synonyms - Wang, Fei; Yang, Bei (Advances in Social Sciences Research Journal, 2019)
As an important yet intricate linguistic feature in English language, synonymy poses a great challenge for second language learners. Using the 100 million-word British National Corpus (BNC) as data and the software Sketch Engine (SkE) as an analyzing tool, this article compares the usage of career and job by conducting the analysis of concordance, collocation, word sketches and sketch difference. The results show that different functions of SkE can make different contributions to the discrimination of career and job. The pedagogical implications of the findings are also discussed.